RESULTS Coaching : the New Essential for School Leaders. - Kee, Kathryn M. (SAGE Publications, 2010)
This resource offers "coach-leaders" tools and strategies for guiding staff to continuously grow and improve, maximize their potential, and create productive school cultures.